2016
DOI: 10.1021/acs.langmuir.6b03405
|View full text |Cite
|
Sign up to set email alerts
|

Bottom-Up Assembly of Molecular Nanostructures by Means of Ferroelectric Lithography

Abstract: Here, we report on the photochemical deposition of Rhodamine 6G (Rh6G) and Alexa647 molecules from aqueous and methanolic solution along 180° ferroelectric (FE) domain walls (DWs) of z-cut lithium niobate (LNO) single crystals. Molecules and FE domains were investigated by means of dynamic-mode AFM, piezoresponse force microscopy (PFM), and confocal scanning fluorescence microscopy. A high deposition affinity for 180° DWs on the LNO surface is observed, leading to the formation of molecular nanowires. Addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…This apparently contradictory behavior represents a limit for the application of PPLN for the directed assembling of NPs in photonic devices. , It is important to understand the dynamic behind this process to precisely design patterned pyroelectric crystals and to control all the forces involved in it. To identify the fundamental mechanism of QD positioning, we performed finite element method (FEM) simulations using a commercial software (COMSOL).…”
Section: Resultsmentioning
confidence: 99%
“…This apparently contradictory behavior represents a limit for the application of PPLN for the directed assembling of NPs in photonic devices. , It is important to understand the dynamic behind this process to precisely design patterned pyroelectric crystals and to control all the forces involved in it. To identify the fundamental mechanism of QD positioning, we performed finite element method (FEM) simulations using a commercial software (COMSOL).…”
Section: Resultsmentioning
confidence: 99%
“…Details on how to prepare and analyze such a single, highly conductive DW can be found in refs. . In brief, the Godau work provided a reliable protocol of how to increase the tilt angles α in sc‐LNO samples; applying a moderate electrical field of ≈60% of the coercive field across the 200 µm thick sample tunes a DW with a diameter in the range of 50 µm to larger bending angles with respect to the sample c ‐axis, hence increasing the DWC.…”
Section: Methodsmentioning
confidence: 99%
“…DWs thus are very promising candidates for both the bottom-up assembly of functional nanoelectronic broad variety of different electronic transport scenarios, such as topological Kondo-Insulators, [21] manganite thin films upon Mott phase transitions, [22] as well as the currents flowing in disordered semiconductors, [23] in composite materials, [24] or in low-dimensional nanostructures [25] like graphene [26] or singlestranded DNA molecules. [17,28,29]. Details on how to prepare and analyze such a single, highly conductive DW can be found in refs.…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, Zhang et al reported that d-cysteine strongly accumulates at (+) domains on the surface of PPLN, 105 and Hauβmann et al describe the nanoscale photodeposition of two organic fluorophores (rhodamine 6G and Alexa fluor 647) over polarized domains of LN. 106 And, in a more biologically-oriented paper, another group recently published that positively-charged tertiary amines functionalizing polyethylene surfaces enhanced osteogenesis of rat bone marrow mesenchymal stem cells as compared with non-functionalized surfaces. 107 The important positive surface charge imposed by the amines induced a robust upregulation of inducible nitric oxide synthase (iNOS) in the attached cells, which drove downstream transcription of osteogenic genes like alkaline phosphatase, Runx-2, OCN and BSP.…”
Section: Molecular Crowdingmentioning
confidence: 99%